DENTAL CARIES STATUS OF PREGNANT WOMEN IN THE WORK AREA OF CIBEUNYING HEALTH CENTER BANDUNG DISTRICT - Marlin Himawati; Putri M; Bima Diaz Candra; Erindya Navika Rizkani; Sarah Aulia Rahmah; Putri Anjani; Gracia Astried Novania Putri (Fakultas Kedokteran Gigi Unjani, 2023)
Riset Kesehatan Dasar (Riskesdas) stated in 2018 that Indonesia's most significant dental problem was tooth decay/cavities/pain (45.3%). Pregnant women are susceptible to dental and oral diseases such as caries and gingivitis if they do not maintain dental and oral hygiene conditions. The study aimed to determine the DMF-T index of pregnant women in Cibeunying Health Center, Bandung Regency, West Java. The study's population was a cross-sectional study of all pregnant women who came to the KIA poly and Posyandu in the working area of ​​the Cibeunying Health Center. A random sampling technique was used to select the subjects. The DMFT index measured the caries index. The results of this study showed that the DMF-T index of pregnant women in the working area of ​​the Cibeunying Health Center was 7.68. Based on the study's results, it was concluded that the caries index in pregnant women is high. DOI : 10.54052/jhds.v2n3.p479-488